Pengaruh Likopen terhadap Penurunan Aktivitas Mitogen-Activated Protein Kinase (MAPK) dan Ekspresi Endothelin-1 (ET-1) pada Kultur Huvecs yang Dipapar Leptin - Fatmawati, Heni; Satuman, Satuman; Rudijanto, Ahmad; Indra, Muhammad Rasjad (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2011)
The effect of obesity on vascular function is mediated by hormon leptin. Leptin has been proved to increaseoxidative stress in endothelial cell. The previous study has proven that leptin caused the endothelial dysfunction asa step of the atherogenesis. Lycopene, an antioxidant, is presumed having the ability to block the atherogenesismechanism, which is stimulated a proinflamatory cytokine and adhesion molecules by MAPK and transcriptionfactor ET-1. Therefore, the aim of this research was to prove and to determine whether lycopene could decreasethe MAPK and ET-1 expression in Human Umbillical Vein Endothelial Cells (HUVECs) culture induced by 500 ng/mlleptin. In vitro study used primary culture of the HUVECs were devided in to 7 groups, there were (1) 0 ng/ml leptinand 0 ìM lycopene, (2) induced by 500 ng/ml leptin for 12 hours, (3) induced by leptin and lycopene with concentration10; 25; 40; 55 and 75 ìM for 12 hours. Then the identification of MAPK was applied by using imunocytochemistrycompared with ELISA procedure on cell endothel culture lysate and ET-1 expression was measured by using RTPCR. It was showed that lycopene 10-25 ìM decreased MAPK and ET-1 expression significantly in HUVECs cultureinduced by leptin 500 ng/ml. Leptin was increased ERK1/2 MAPK and ET-1 expression in HUVECs culture and candecrease by lycopene. Optimum dose of lycopene is 10-25 ìM.